2008
DOI: 10.1177/154193120805201908
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Automation Reliability on User Automation Trust and Reliance in a Search-and-Rescue Scenario

Abstract: Advances in modern day technology are rapidly increasing the ability of engineers to automate ever more complicated tasks. Often these automated aids are paired with human operators who can supervise their work to ensure that it is free of errors and to even take control of the system if it malfunctions (e.g., pilots supervising an autopilot feature). The goal of this collaboration, between humans and machines, is that it can enhance performance beyond what would be possible by either alone. Arguably the succe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 4 publications
2
20
0
Order By: Relevance
“…Several different aspects of performance have been studied. First, numerous studies have shown that the reliability and validity of an automated system's functions are important antecedents of trust (Bailey & Scerbo, 2007;Madhavan & Wiegmann, 2007a;Oduor & Campbell, 2007;Seong & Bisantz, 2008;Ross, 2008;Ross, Szalma, Hancock, Barnett, & Taylor, 2008;Sanchez et al, 2004;Wetzel, 2005). Reliability refers to the consistency of an automated system's functions, and validity refers to the degree to which an automated system performs the intended task.…”
Section: Learned Trustmentioning
confidence: 99%
“…Several different aspects of performance have been studied. First, numerous studies have shown that the reliability and validity of an automated system's functions are important antecedents of trust (Bailey & Scerbo, 2007;Madhavan & Wiegmann, 2007a;Oduor & Campbell, 2007;Seong & Bisantz, 2008;Ross, 2008;Ross, Szalma, Hancock, Barnett, & Taylor, 2008;Sanchez et al, 2004;Wetzel, 2005). Reliability refers to the consistency of an automated system's functions, and validity refers to the degree to which an automated system performs the intended task.…”
Section: Learned Trustmentioning
confidence: 99%
“…It is acknowledged that perceived reliability is only one aspect of user trust (Hoff & Bashir, 2015;McCarley, Wiegmann, Wickens, & Kramer, 2003). However, using perceived reliability as a metric to quantify trust has been shown to be an effective means with which to measure how much a user will trust in an automated decision aid (Ross et al, 2008). This research uses this same metric with an autonomous agent rather than just an automated decision aid.…”
Section: Dependent Variablementioning
confidence: 99%
“…One aspect of successful teams is trust between teammates. Trust in automation is defined as the human user's confidence that the automated system will help the user achieve his or her goals in environments of uncertainty and vulnerability (Ross et al, 2008). Research has shown that in most environments, performance is higher when the user trusts the automation to perform its role (Endsley, 2015;Ho et al, 2005;.…”
mentioning
confidence: 99%
“…As technologies improved, autonomous systems gained the capability to diagnose failure or recommend operator actions. Ross et. al.…”
Section: Human Reliancementioning
confidence: 99%